Management of Complex Anal Fistulas - Bubbers, Emily J.; Cologne, Kyle G. (Clinics in Colon and Rectal Surgery, 2016)
Complex anal fistulas require careful evaluation. Prior to any attempts at definitive repair, the anatomy must be well defined and the sepsis resolved. Several muscle-sparing approaches to anal fistula are appropriate, and are often catered to the patient based on their presentation and previous repairs. Emerging technologies show promise for fistula repair, but lack long-term data.
Keywords: transsphincteric fistula; advancement flap; anal fistula